Tuberculosis of Left Clavicle in a Young Boy - Jana, Pulak Kumar; Das, Ira; Bairagya, Tapan Das; Das, Sibes Kumar (Journal of Medicine, 2012)
DOI: http://dx.doi.org/10.3329/jom.v13i1.10092 JOM 2012; 13(1): 123